SPATIAL DISTRIBUTION OF BRINJAL SHOOT AND FRUIT BORER, LEUCINODES ORBONALIS GUEN (LEPIDOPTERA: PYRALIDAE) - SINGH, R.K. RADHAKRISHORE; SINGH, T.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Spatial distribution of brinjal shoot and fruit borer, Leucinodes orbonalis was studied. Various indices of dispersion viz variance to mean ratio, dispersion parameter-k, mean crowding, Lloyds index of patchiness, Iwao’s regression fitting and Taylor’s power law revealed that the pest followedcoñtagious population. The confirmation for the clumped distribution was also obtained from the value of mean crowding and Lloyd’s index of patchiness, which were greater than unity.